Hubungan Kreativitas, Efikasi Diri dan Intensi Berwirausaha pada Mahasiswa - Rr. Ponco Dewi Karyaningsih; Agus Wibowo (Faculty of Economics, State University of Jakarta., 2017)
This article aims to determine the relationship between creativity, self efficacy and student entrepreneurship intent of Faculty of Economics (FE), State University of Jakarta (UNJ) This research uses survey method with correlation approach.The results showed that there is a significant correlation between creativity, self efficacy and intent entrepreneurship of FE UNJ students where the result of calculation of double correlation coefficient test (Ry.12) = 0,635 and F count (F Change) = 49,785, and p-value = 0,000 <0,05, and coefficient of determination (R square) = 0,404 , which implies that creativity (X1) and self efficacy (X2) together influence 40.4% of entrepreneurship intentions (Y). Keywords: Creativity, Self Efficacy, Entrepreneurship Intention